CRITERIA FOR EVALUATING THE QUALITY OF BREAD AND BAKERY PRODUCTS IN UKRAINE (Development Service Industry Management, 2023)
The article examines the criteria for evaluating the quality of bread and bakery products in Ukraine. It is noted that currently the main problem for bread producers is the increase of electricity and fuel for transport services. In addition, bakers currently receive low wages, which may affect the quality of bread in the future. It was determined that the most important criteria for bread and bakery products for the consumer are freshness and quality, and only then the price. The quality of bread and bakery products was analyzed according to organoleptic and physicochemical indicators. It is noted that due to the low baking qualities of flour, violations of the conditions of storage of raw materials and its preparation for production, non-compliance with the recipe, the technological regime of dough preparation, proofing, baking, and storage of bread leads to diseases of bakery products that affect the human body. It was concluded that today it is possible to improve the quality of bread in various ways. This is a clear imitation of the technological process, the use of quality ingredients, as well as special additives, for example, malt, fastids, whey, etc. This characteristic of "healthy" bread: yeast-free, whole-grain, multi-grain and gluten-free. It has been noted that colored bakery products have been in great demand recently. To make bakery products colorful - you don't need artificial dyes and new equipment, it is enough to use dried vegetables, fruits, herbs, spices, natural plant powders and juices. It was determined that despite the variety of types of bread in the "healthy" segment, wheat bread is in the greatest demand among consumers. It is noted that there is a constant increase in the price of bread, the reasons are the war in Ukraine, the increase in the price of gas, the fall in the hryvnia exchange rate and the increase in fuel prices. These are really important factors that influence the formation of the price of bread. It was concluded that the state of the bakery industry in Ukraine was influenced by the change in the culture of consumption and the increase in the price of bread. Demand for flour products enriched with vitamins, minerals and trace elements has increased, and this leads to the growth of food trends.
Keywords: bread and bakery products; bread quality; colored bakery products